Prevalence and risk factors for newborn anemia in southwestern Uganda: a prospective cohort study - Ngonzi, Joseph; Tibaijuka, Leevan; Kintu, Timothy Mwanje; Kihumuro, Raymond Bernard; Onesmus, Ahabwe; Onesmus, Byamukama; Adong, Julian; Salongo, Wasswa; Boatin, Adeline A.; Bebell, Lisa M. (Research square, 2023)
Introduction: The global prevalence of anemia in pregnancy is about 42%, and in sub-Saharan Africa, the prevalence of newborn anemia ranges from 25–30%. Anemia in newborn babies may cause complications such as delayed brain maturation and arrested growth. However, there is limited data on prevalence of newborn anemia and its risk factors in people living in resource-limited settings. Objectives: We determined the prevalence and risk factors for newborn anemia and its correlation with maternal anemia in southwestern Uganda. Methods: This was a prospective cohort study of 352 pregnant women presenting to Mbarara Regional Referral Hospital for delivery. We collected maternal blood in labor and umbilical cord blood from the placental vein, as a proxy for newborn hemoglobin. We estimated hemoglobin using a point-of-care Hemocue machine. We used summary statistics to characterize the cohort, and compared demographic characteristics and outcomes using Chi-square, t-test, and Wilcoxon Ranksum analyses. We defined newborn anemia as umbilical cord hemoglobin < 13g/dl and estimated the relationship between maternal and umbilical cord hemoglobin using linear regression analysis, adjusting for potential confounders. Results: The prevalence of newborn anemia was 17%. The average maternal parity was significantly higher for anemic and non-anemic newborns (3.5 versus 2.8, P = 0.01). Mean age [SD] was significantly lower for participants with umbilical cord hemoglobin < 13g/dl than those > = 13 g/dl, (26 [5.6] versus 28 [6.3], P = 0.01). In multivariable linear regression analysis, a 1-point decrease in maternal hemoglobin was associated with a 0.14-point decrease in umbilical cord hemoglobin (P = 0.02). Each one-unit increase in maternal parity was associated with a 0.25-point decrease in umbilical cord hemoglobin (P = 0.01). Cesarean delivery was associated with a 0.46-point lower umbilical cord hemoglobin level compared to vaginal delivery (P = 0.03). Conclusions: We found a significant correlation between maternal and newborn hemoglobin levels, underscoring the importance of preventing and correcting maternal anemia in pregnancy. Furthermore, maternal anemia should be considered a risk factor neonatal anemia.
Keywords: Maternal anemia; Newborn anemia; Cord blood; Risk factors; Prevalence; Uganda; Prospective cohort